Thermal inactivation of Salmonella in ready-to-use therapeutic food and prediction using neural network and conventional models - Zhen Jia; Patrick S. Saengpet; Hua Wang; Genevieve H. Flock; Jeanette M. Andrade; Kelsey Bowen; Harshadha Kondapalli; Jiajia Wen; Ren Yang; Katherine Thompson-Witrick; Rufino Perez; Juan E. Andrade Laborde; et al. (Food Research International, 2026)

Petiole Nitrate Analysis: A Diagnostic Method for Optimizing Nitrogen Management in Potato - C. M. Giletto; W. Carciochi; S. E. Silva; M. N. Cassino; S. Rodriguez; J. C. Laborde Amador; E. C. Zamuner; N. I. Reussi Calvo (Potato Research, 2026)

A Simple Model to Estimate the Economic Optimum Nitrogen Rate in Potato Using Vegetation Indices - Claudia M. Giletto; W. D. Carciochi; F. M. Inchauspe; S. E. Silva; M. N. Cassino; V. Ortega; S. Rodriguez; J. C. Laborde Amador; N. Reussi Calvo (Potato Research, 2025)

Exploring the potential biopesticide application of nemertide alpha-1 on parasitic and disease vector mosquitoes - Quentin Laborde; Melika Hajkazemian; Justine Bonnassieux; Håkan S. Andersson; Ulf Göransson; S. Noushin Emami (Phytochemistry Letters, 2025)

Peptide toxins from ribbon worms (Nemertea) - Erik Jacobsson; Quentine Laborde; Håkan S. Andersson; Ulf Göransson (Phytochemistry Letters, 2025)

Eight weeks of high-intensity interval training versus stretching do not change the psychoneuroendocrine response to a social stress test in emotionally impulsive humans - F. Javelle; W. Bloch; U. Borges; T. Burberg; B. Collins; N. Gunasekara; T. J. Hosang; T. Jacobsen; S. Laborde; A. Löw; A. Schenk; M. L. Schlagheck; et al. (European Journal of Applied Physiology, 2024)
Purpose Research supports physical activity as a method to heighten stress resistance and resilience through positive metabolic alterations mostly affecting the neuroendocrine system. High-intensity interval training (HIIT) has been proposed as a highly effective time-saving method to induce those changes. However, existing literature relies heavily on cross-sectional analyses, with few randomised controlled trials highlighting the necessity for more exercise interventions. Thus, this study aims to investigate the effects of HIIT versus an active control group on the stress response to an acute psychosocial stressor in emotionally impulsive humans (suggested as being strong stress responders). Methods The study protocol was registered online (DRKS00016589) before data collection. Sedentary, emotionally impulsive adults (30.69 ± 8.20 y) were recruited for a supervised intervention of 8 weeks and randomly allocated to either a HIIT ( n = 25) or a stretching group ( n = 19, acting as active controls). Participants were submitted to a test battery, including saliva samples, questionnaires (self-efficacy- and perceived stress-related), visual analogue scales (physical exercise- and stress-related), and resting electroencephalography and electrocardiography assessing their reaction to an acute psychological stressor (Trier Social Stress Test) before and after the exercise intervention. Results HIIT increased aerobic fitness in all participants, whereas stretching did not. Participants from the HIIT group reported perceiving exercising more intensively than those from the active control group ( ƞ p 2 = 0.108, p = 0.038). No further group differences were detected. Both interventions largely increased levels of joy post-TSST ( ƞ p 2 = 0.209, p = 0.003) whilst decreasing tension ( ƞ p 2 = 0.262, p < 0.001) and worries ( ƞ p 2 = 0.113, p = 0.037). Finally, both interventions largely increased perceived levels of general self-efficacy ( ƞ p 2 = 0.120, p = 0.029). Conclusion This study suggests that 8 weeks of HIIT does not change the psychoneuroendocrine response to an acute psychological stress test compared to an active control group in emotionally impulsive humans. Further replications of supervised exercise studies highly powered with active and passive controls are warranted.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

General and specific combining abilities in a maize (Zea mays L.) test-cross hybrid panel: relative importance of population structure and genetic divergence between parents - A. Larièpe; L. Moreau; J. Laborde; C. Bauland; S. Mezmouk; L. Décousset; T. Mary-Huard; J. B. Fiévet; A. Gallais; P. Dubreuil; A. Charcosset (Theoretical and Applied Genetics, 2017)

Dent and Flint maize diversity panels reveal important genetic potential for increasing biomass production - R. Rincent; S. Nicolas; S. Bouchet; T. Altmann; D. Brunel; P. Revilla; R. A. Malvar; J. Moreno-Gonzalez; L. Campo; A. E. Melchinger; W. Schipprack; E. Bauer; et al. (Theoretical and Applied Genetics, 2014)

Revisiting tree-migration rates: Abies alba (Mill.), a case study - Rachid Cheddadi; H. John B. Birks; Pedro Tarroso; Sascha Liepelt; Dusan Gömöry; Stefan Dullinger; Eliane S. Meier; Karl Hülber; Luigi Maiorano; Henri Laborde (Vegetation History and Archaeobotany, 2014)

Building the niche through time: using 13,000 years of data to predict the effects of climate change on three tree species in Europe - L. Maiorano; R. Cheddadi; N. E. Zimmermann; L. Pellissier; B. Petitpierre; J. Pottier; H. Laborde; B. I. Hurdu; P. B. Pearman; A. Psomas; J. S. Singarayer; O. Broennimann; et al. (Global Ecology and Biogeography, 2013)
Aim Species distribution models (SDMs) based on current species ranges underestimate the potential distribution when projected in time and/or space. A multi‐temporal model calibration approach has been suggested as an alternative, and we evaluate this using 13,000 years of data. Location Europe. Methods We used fossil‐based records of presence for Picea abies , Abies alba and Fagus sylvatica and six climatic variables for the period 13,000 to 1000 yr bp . To measure the contribution of each 1000‐year time step to the total niche of each species (the niche measured by pooling all the data), we employed a principal components analysis (PCA) calibrated with data over the entire range of possible climates. Then we projected both the total niche and the partial niches from single time frames into the PCA space, and tested if the partial niches were more similar to the total niche than random. Using an ensemble forecasting approach, we calibrated SDMs for each time frame and for the pooled database. We projected each model to current climate and evaluated the results against current pollen data. We also projected all models into the future. Results Niche similarity between the partial and the total‐SDMs was almost always statistically significant and increased through time. SDMs calibrated from single time frames gave different results when projected to current climate, providing evidence of a change in the species realized niches through time. Moreover, they predicted limited climate suitability when compared with the total‐SDMs. The same results were obtained when projected to future climates. Main conclusions The realized climatic niche of species differed for current and future climates when SDMs were calibrated considering different past climates. Building the niche as an ensemble through time represents a way forward to a better understanding of a species' range and its ecology in a changing climate.

Inflow intrusions at multiple scales in a large temperate lake - S. Laborde; J. P. Antenucci; D. Copetti; J. Imberger (Limnology and Oceanography, 2010)
Lake Como receives inflows of vastly varying scales. The majority of the lake's water comes from the alpine inflows to the north, and much smaller inflows supply large amounts of pollutants in the south. We combined various data sets with a three‐dimensional hydrodynamic model to investigate the processes affecting the fate of these inflows with potential applications for management responses to both pollution and climate change effects. During the stratified period inflow waters from the northern alpine sources intrude in the metalimnion, undergo a deflection due to the Earth's rotation, and subsequently affect local flushing in a semi‐closed embayment receiving the shallower intrusions of the small polluted inflows.

Evaluation of ibuprofen versus aspirin and paracetamol on efficacy and comfort in children with fever - E. Autret; J. Reboul-Marty; B. Henry-Launois; C. Laborde; S. Courcier; J. M. Goehrs; G. Languillat; R. Launois (European Journal of Clinical Pharmacology, 1997)